Fabrication of Sub-Micron Near Stoichiometric NdFeB Magnetic Powder through HDDR Processing Route - Shaaban, Azizah (2007)
Homogenized Near-Stoichiometric NdFeB alloys of composition Nd12.7FesuB6.o and Nd12.2Fes1.2Bs.9Zro.1 were Hydrogenated and disproportionate at 850°C for 30 minutes. All Nd2Fe14B phase were fully converted into NdH3, Fe38 and Fe. The recombination process produces sub-micron sizes ( ~ 0.3 μm) of Nd2Fe148 grains at an optimum temperature of 880°C. Zr addition into the NdFeB alloy inhibits grain growth during the recombination process.